Factors Influencing the Interest of Youth In Rice Farming at Trenggalek Regency - Devan Adhitya Firmansyah; Endang Yektiningsih; Dona Wahyuning Laily (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
This research investigates the factors influencing the interest of village youth in rice farming in Banjar Village, Panggul Subdistrict, Trenggalek Regency, conducted from October until December 2023. Factors such as motivation, perception of agriculture, social environment, and government support are examined to understand their impact on youth interest in farming. The declining youth labor force in agriculture poses a significant challenge, threatening the sustainability of family farms and agricultural development. The research employs a Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis to measure the relationships between the identified factors and youth interest in farming. Data collection involves primary and secondary sources, with respondents providing information on demographics, current occupation, motivation, perception of income, risk, work environment in rice farming, and the influence of family and school environments. The purposive method was used within this article, counting 50 local youth aged 15-30 years old with an experience or family background as a farmer. The analysis confirms that youth perception of agriculture, social environment, and government support significantly affect (<0,05) youth interest in rice farming, while motivation alone does not significantly impact. The study's measurement instruments demonstrate satisfactory convergent validity, construct validity, and composite reliability. Recommendations include maintaining positive perceptions of agriculture, educating rural communities on its importance, and enhancing government support through subsidies, access to capital, training, and extension programs. The research provides valuable insights for promoting agricultural development and ensuring the continuation of family farms by addressing the factors that influence youth interest in farming.